Microplastics and Their Possible Effects on Seafoods - Türkmen, Mustafa; Öztas, Fulya; Öztas, Haydar (Research Advances in Environment, Geography and Earth Science Vol. 1, 2024)
It is known that plastics and microplastics, which are their breakdown products, have harmful effects on human health and contain some commonly used chemicals. It is known that plastic particles, which are increasingly becoming a global problem, have many negative effects on the environment and human health. People are constantly exposed to plastic through contaminated food, misused plastic products, atmospheric fallout and urban dust containing microplastics, personal care products (PCPs) and synthetic clothing. some plastic products, such as bisphenol (BPA), polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), dichlorobiphenyls trichloroethanes (DDTs), and PFOs contain toxic additives, thus posing a risk factor for marine organisms. Therefore, assessing the possible impact of microplastic levels on marine food chains and humans is considered important for human health. Although definitive evidence linking microplastic consumption to human health is not sufficient, the results obtained from studies conducted on humans exposed to high concentrations of microplastics, model animal and cell culture experiments, it is possible to say that the effects of microplastics trigger some negative developments related to the immune, neurological, and hormonal systems. Nonetheless, knowledge on microplastic toxicity is still limited and largely influenced by exposure concentration, particle properties, adsorbed contaminants, tissues involved and individual susceptibility, requiring further research.